2023
DOI: 10.1051/0004-6361/202244456
|View full text |Cite
|
Sign up to set email alerts
|

Imaging-spectroscopy of a band-split type II solar radio burst with the Murchison Widefield Array

Abstract: Type II solar radio bursts are caused by magnetohydrodynamic (MHD) shocks driven by solar eruptive events such as coronal mass ejections (CMEs). Often, both fundamental and harmonic bands of type II bursts are split into sub-bands, which are generally believed to be coming from upstream and downstream regions of the shock; however, this explanation remains unconfirmed. Here, we present combined results from imaging analyses of type II radio burst band splitting and other fine structures observed by the Murchis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Though the early classification has stood the test of time for some seventy years, every significant advancement in instrumentation capabilities has brought about discoveries of previously unappreciated aspects of emissions at finer scales, often leading to elaborate sub-classification of each burst type. The most recent wave of such discoveries is in progress today, owing to instruments like the MWA and LOFAR (e.g., Suresh et al 2017;Kontar et al 2017;Sharykin et al 2018;Mohan et al 2019a, b;Magdalenić et al 2020;Mohan 2021a;Mondal & Oberoi 2021;Bhunia et al 2023). Of the various solar burst types, we focus on the ones which had garnered a lot of attention in the recent past primarily owing to some notable discoveries.…”
Section: Studies Of Solar Radio Burstsmentioning
confidence: 99%
“…Though the early classification has stood the test of time for some seventy years, every significant advancement in instrumentation capabilities has brought about discoveries of previously unappreciated aspects of emissions at finer scales, often leading to elaborate sub-classification of each burst type. The most recent wave of such discoveries is in progress today, owing to instruments like the MWA and LOFAR (e.g., Suresh et al 2017;Kontar et al 2017;Sharykin et al 2018;Mohan et al 2019a, b;Magdalenić et al 2020;Mohan 2021a;Mondal & Oberoi 2021;Bhunia et al 2023). Of the various solar burst types, we focus on the ones which had garnered a lot of attention in the recent past primarily owing to some notable discoveries.…”
Section: Studies Of Solar Radio Burstsmentioning
confidence: 99%
“…Imaging spectroscopy of type II radio bursts can be used to locate shock-accelerated electron beams (e.g., Zucca et al 2018;Morosan et al 2019). With the new availability of low-frequency radio imaging, recent studies have provided improved multifrequency images of type II bursts and associated fine structures (e.g., Zucca et al 2018;Morosan et al 2019;Chrysaphi et al 2020;Bhunia et al 2023). For example, Zucca et al (2018) used the tied-array beam observation mode (Morosan et al 2014) of the Low Frequency Array (LOFAR; van Haarlem et al 2013) on a type II solar radio burst.…”
Section: Introductionmentioning
confidence: 99%
“…Morosan et al (2019) also used tiedarray beam imaging observations from LOFAR to image herringbone bursts and identified the presence of shock-accelerated They find that the radio source is located about 0.5 solar radii above a solar jet, which suggests the type II burst was generated by a jet-driven piston shock, instead of a CME-driven shock wave. In another study with the Murchison Widefield Array (MWA), Bhunia et al (2023) performed radio imaging of a band-splitting type II event at multiple frequencies and found that the radio source is located at multiple locations close to the shock. Spatially resolved radiometry analysis is a powerful tool for analyzing the electron beam locations and propagation in detail, by imaging the fine structures in dynamic spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Type II bursts are associated with expanding CME-driven shock waves (e.g., Zimovets et al 2012;Zucca et al 2014Zucca et al , 2018Mancuso et al 2019; Morosan et al 2020a) and in rare cases with the expansion of a coronal shock wave in the absence of a CME (e.g., Magdalenić et al 2012;Su et al 2015;Maguire et al 2021;Morosan et al 2023). Type II bursts often show splitbands of emission that are believed to originate from different regions of the shock front (e.g., Holman & Pesses 1983;Bhunia et al 2023) or from the upstream and downstream regions of the shock (e.g., Smerd et al 1975;Kumari et al 2017). Herringbone bursts usually stem from a type II lane or "backbone", however, they are sometimes observed without an accompanying type II burst (Holman & Pesses 1983;Cane & White 1989;Mann & Klassen 2005;Morosan et al 2019).…”
Section: Introductionmentioning
confidence: 99%